Effect of toxic quantities of lead salts in soil on the yield and lead content in cloche tomatoes - Tanevski, Boris; Gjorgiev, Mitko (Macedonian Journal of Ecology and Environment, 1994)
The effect of 10, 20, 40, 60 and 80 g per 8 kg soil oflead nitrate, lead chloride and lead acetate on the yield and lead content in the cloche tomatoes of the sort „Sobeto, at the 35-th, 64-th and 90-th days after application of the lead salts was followed in the pot experiments in cloche conditions.